Bioaccessibility of Copper, Molybdenum and Zinc from Selected Oilseed Cakes Using Three Stage In Vitro Technique - Gupta, Shiva; Tomar, S.K.; Mani, Veena; Kumar, R. Dhinesh; Parihar, Deepti; Anjila Kujur, S.T. (Indian Journal of Animal Nutrition, 2018)
The study was conducted to determine chemical composition, in vitro dry matter digestibility (IVDMD) and bioaccessibility of (%) of copper (Cu), molybdenum (Mo) and zinc (Zn) in mustard (MC), cotton seed (CSC) and maize germ oil cake (MGOC). The values of DM, OM, CP, EE, NDF, ADF and TA in MC were 92.27, 92.43, 38.36, 8.17, 28.11, 21.32 and 7.57%, respectively and the corresponding values in CSC were 92.16, 92.91, 21.11, 6.26, 38.33, 31.14 and 7.09% and MGOC were 93.72, 96.42, 18.56, 8.86, 34.60, 23.71 and 3.58%. The MC, CSC and MGOC had Cu content of 9.87, 11.28 and 8.62 ppm, Mo content of 1.52, 1.69 and 1.12 ppm and Zn level of 58.94, 38.93 and 28.21 ppm, respectively. IVDMD (%) was found to be the highest for MC (68.42±0.35) and the lowest for CSC (59.71±1.07). Bioaccessibility (%) of Cu and Zn was lower (P<0.05) at ruminal stage than abomasal and intestinal stage in all oilseed cakes. The bioaccessibility of Cu was higher in MC (70.99±0.39%) followed by MGOC (68.66±0.12%) and CSC (65.33±0.19%). The bioaccessibility of Zn was higher (P<0.05) in MC (45.00±1.15), followed by MGOC (42.00±0.57) and CSC (38.03±0.67). Bioaccessibility (%) of Mo was numerically increased from ruminal to intestinal stage and overall bioaccessibility (%) of Mo varied from 83.33±0.84 to 85.00±0.23 in all three oilseed cakes with no significant difference among these oilseed cakes.